ESTIMATION OF DUST DISPERSE COMPOSITION OF FERROUS CASTING SECTION - I.A. IVANOVA; V.Y. MANOKHIN (Advanced Engineering Research, 2010)
Theoretical and experimental data on chemical, disperse composition of foundry dust are analyzed. Parameters of true density of dust coming out of sandblast machines and the section of castings shakeout from moulds of PLC “Rostvertol” have been determined experimentally. Technical measures on pollution reduction of working zones of these sections are proposed.